Cooperative networking - Obaidat, Mohammad S. (Mohammad Salameh), 1952-; Misra, Sudip (Wiley, 2011)
This book focuses on the latest trends and research results in Cooperative Networking This book discusses the issues involved in cooperative networking, namely, bottleneck resource management, resource utilization, servers and content, security, and so on. In addition, the authors address instances of cooperation in nature which actively encourage the development of cooperation in telecommunication networks. Following an introduction to the fundamentals and issues surrounding cooperative networking, the book addresses models of cooperation, inspirations of successful cooperation from nature and society, cooperation in networking (for e.g. Peer-to-Peer, wireless ad-hoc and sensor, client-server, and autonomous vehicular networks), cooperation and ambient networking, cooperative caching, cooperative networking for streaming media content, optimal node-task allocation, heterogeneity issues in cooperative networking, cooperative search in networks, and security and privacy issues with cooperative networking. It contains contributions from high profile researchers and is edited by leading experts in this field. Key Features: -- Focuses on higher layer networking -- Addresses the latest trends and research results -- Covers fundamental concepts, models, advanced topics and performance issues in cooperative networking -- Contains contributions from leading experts in the field -- Provides an insight into the future direction of cooperative networking -- Includes an accompanying website containing PowerPoint slides and a glossary of terms. This book is an ideal reference for researchers and practitioners working in the field. It will also serve as an excellent textbook for graduate and senior undergraduate courses in computer science, computer engineering, electrical engineering, software engineering, and information engineering and science.